The DIVING3D Survey - Deep IFS View of Nuclei of Galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Steiner, J. E.; Menezes, R. B.; Ricci, T. V.
Abstract: The DIVING 3D Survey (Deep Integral Field Spectrograph View of Nuclei of Galaxies) aims to observe, with high signal/noise and high spatial resolution, a statistically complete sample of southern galaxies brighter than B = 12.0 The main objectives of this survey are to study: 1) the nuclear emission line properties; 2) the circumnuclear emission line properties; 3) the central stellar kinematics and 4) the central stellar archaeology. Preliminary results of individual or small groups of galaxies have been published in 18 papers.